2016
DOI: 10.1007/s10068-016-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total antioxidant potential, and total phenolic, nitrate, sugar, and organic acid contents in beetroot juice, chips, powder, and cooked beetroot

Abstract: Beetroot is a vegetable rich in nitrate (NO ), antioxidants and phenolic compounds that are related to improvements in cardiovascular function and exercise performance. However, it is unknown if convenient forms of beetroot administration provide different amounts of these nutrients. The total antioxidant potential (TAP), total phenolic (TPC), sugar, organic acid, and NO contents of beetroot juice (BJ), chips (BC), powder (BP), and cooked beetroot (CB) were compared. Significant (<0.01) differences in chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 36 publications
2
44
1
1
Order By: Relevance
“…Wruss et al (2015) observed antioxidant capacity in the range of 19.7 to 37.9 mM TE in seven varieties of beetroot grown in upper Austria. Similarly, Vasconcellos et al (2016) found that beetroot juice contained 80.48% of total antioxidant activity.…”
Section: Beetroot Juicementioning
confidence: 93%
“…Wruss et al (2015) observed antioxidant capacity in the range of 19.7 to 37.9 mM TE in seven varieties of beetroot grown in upper Austria. Similarly, Vasconcellos et al (2016) found that beetroot juice contained 80.48% of total antioxidant activity.…”
Section: Beetroot Juicementioning
confidence: 93%
“…Beetroot contains pigments called betalains that are composed of vulgaxanthin I, vulgaxanthin II, indicaxanthin, betanin, prebetanin, isobetanin, neobetanin and a pool of phenolic compounds that includes phenolic acids, flavonoids, organic and inorganic acids [13]. Beetroot also includes smaller amounts of other compounds, such as ascorbic acid, which may further increase the total antioxidant capacity and enhance the body's ability to fight with reactive oxygen species [14]. Researchers have probed the effects of acute and chronic consumption of beetroot juice in individuals and athletes [15][16][17].…”
Section: Research In Molecular Medicine (Rmm)mentioning
confidence: 99%
“…Dietary administration of beetroot, a vegetable NO 3 − source, can be conducted through several types of formulations, in order to provide a convenient and alternative source of beetroot, instead of consuming the whole vegetable. Some beetroot formulations must be offered in large amounts to reach effective NO 3 − concentrations, making it difficult to convince individuals to adhere to certain proposed interventions [7][8][9]. In this context, this paper discusses the recent advances in beetroot administration, pointing out plant species, nutritional composition and the effect of the ingestion of different beetroot formulations on NO production and the ensuing effects on hemodynamic parameters.…”
Section: Dietary Nomentioning
confidence: 99%
“…Kaimainen et al [74] and Vasconcellos et al [7] prepared beetroot powder after freeze-drying beetroot juice in a spray dried system. Vasconcellos et al [7] also produced beetroot chips.…”
Section: Production Of Different Beetroot Formulationsmentioning
confidence: 99%
See 1 more Smart Citation